Cerebral Venous Sinus Thrombosis during Everest Expedition: A Case Report and Review of the Literature. (31st October 2016) - Khanal, P.; Thapa, L.; Shrestha, A. M.; Bhattarai, S.; Sapkota, D.; Sharma, N.; Devkota, U. P.
Abstract : Cerebral venous sinus thrombosis (CVST) is a rare but serious disorder that is associated with a poor clinical outcome. We report a 35-year-old man who had a severe headache and diplopia while climbing Mount Everest. His MR venography showed right transverse and right sigmoid sinus thrombosis. He improved on anticoagulant and symptomatic measures. Cerebral venous sinus thrombosis at high altitude is discussed.